Near Peer Learning in Neurology Residency Training on Electromyography - TAN Ying; HONG Yuehui; LI Jia; SHEN Dongchao; SHI Jiayu; YIN Hexiang; ZHOU Lixin; NI Jun; ZHU Yicheng (Xiehe Yixue Zazhi)
ObjectiveTo explore the effectiveness of "near peer learning" (NPL) in the electromyography(EMG)teaching module for neurology residents.MethodsThe Department of Neurology, Peking Union Medical College Hospital implemented an NPL instructional design for a course on EMG for residents from November 2020 to March 2024. This teaching session was held annually, in which senior residents instructed juniors who were 1 or 2 years earlier in their training. The residents participated in the pre-course/post-course tests and completed a feedback survey at the end of the session. This evaluation method was used to understand the effectiveness of the NPL intervention in EMG teaching.ResultsOver four years, a total of 83 residents participated. Among them, there were 24 postdoctoral students, 52 postgraduates and 7 junior residents. The results showed that the post-course test scores were significantly improved compared with pre-course test scores (74.33±2.43 vs. 70.11±2.49, P=0.005), with the most remarkable improvements seen for "tutees" (73.84±20.53 vs. 70.29±21.46, P=0.020), postgraduates (74.04±22.51 vs. 68.97±21.40, P=0.009), first-year residents (70.19±4.02 vs. 63.59±3.59, P=0.040) and first-time participating residents (65.23±3.24 vs. 60.97±3.21, P=0.030). The post-program feedback showed that both tutors and tutees thought highly of NPL, believing that it enabled them to gain knowledge and helped them to improve teaching skills.ConclusionsThe NPL intervention is suitable for the teaching of EMG, because of its contribution to knowledge acquisition and basic clinical skills improvement. The NPL is worth replicating in other teaching and learning programs.